8.8k views
3 votes
Simplify 11 x - 7 - 3 x + 4

User Kujawk
by
4.6k points

2 Answers

5 votes

Answer:

8x - 3

Explanation:

Simplify 11 x - 7 - 3 x + 4........................................................................(the question)

in order to simplify 11 x - 7 - 3 x + 4

we first of all rearrange the expression in order words collecting the like terms.

we have,

=11x-3x-7+4

=8x -7+4

=8x - 3

therefore the simplified form of the expression 11 x - 7 - 3 x + 4 is

8x - 3

User Aerim
by
4.8k points
6 votes

To simplify this expression, we can combine like terms.

= 11x - 7 - 3x + 4

= (11x - 3x) + (-7 + 4)

= 8x - 3

Best of Luck!

User Plof
by
5.3k points